Survey on Classification of Rice Grains Using Neural Network - Bhensjaliya, A.H; Vasava, H.D (International Journal of Computer Sciences and Engineering, 2019)
The Rice is a very useful fool for human .Basically, it is cropped the all human consumes in the overall world, mostly in Asian countries. Basically, it is classified based on the grain shapes; color, etc. This paper presents the use of machine vision system for the grain classification. Different features of the rice grain are depending on different rice grains. An automated system is introduced which can be used for rice grain type identification and classification where the digital image is classified. Images are acquired for the rice using camera. In that , Image processing techniques, segmentations, feature extractions are performed on the acquire images. That can be extracted features from the rice grain in non – contact manner. In this we also discuss and suggesting methods classify seven varieties of rice and it also find the percentage of purity of rice using the grain the techniques of image processing based on the several features such as major axis length, minor axis length, Area etc.